Pengaruh Game Online Terhadap Perilaku Sosial Pada Siswa - Yenti Arsini; Rahmah Yani; Shopiyyah Nazwa (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
One result of the growth of internet media which is now widely used is online games. Games that can only be played digitally or online require the device to be linked to the Internet. Technological developments have had a huge impact on everyone's lives regardless of age, from children to adults. With the development of technology, it makes it easier for everything that is needed, starting from accessing jobs, easily getting information, being able to help long-distance communication and entertainment. There are also examples of very rapid technological developments experienced by children, such as online games. With online games, it will affect students' attitudes in the form of positive and negative impacts. Everything that is created must have positive and negative sides, therefore online games also have both sides.